The principle of averaging for multi-dimentional differential equations of the first order - Strygin, A. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. В. Стрыгин. Принцип усреднения для многомерных дифференциальных уравнений первого порядка V. Stryginas. Vidurkio radimo pirmos eilės daugiamatėms diferencialinėms lygtims principas